À contrecœur, de bon cœur, de tout cœur : de la compositionnalité des locutions figées - Bertin, Thomas (Kalbotyra, 2021)
This study deals with meaning construction in idiomatic phrases (locutions figées/figements). We focus on three French idioms involving the word cœur (à contrecœur, de bon cœur, de tout cœur). To begin, we give a brief account of idiomaticity’s typical criteria, insisting on the common idea that idioms are semantically opaque (non-compositional): their meanings are not a combination of literal meanings (Gross 1996). We argue that another point of view is productive. Indeed, using the notion of “holistic compositionality” (Gosselin 2013), we investigate the way meaning may arise from the combination of words’ abstract semantic contributions (compositionality principle) and take shape contextually (contextuality principle). The primary goal of the study is to analyze the meaning of à contrecœur, de bon cœur, de tout cœur using this approach – which happens to be more accurate than the literal meaning combination approach. To achieve this goal for each of these three idioms: (1) we examine a sample of 200 utterances (and the contexts in which they occur) coming from a large data-source (frWaC) and (2) we take advantage of previous semantic descriptions of cœur (Bertin 2018, 2019), contre (Amiot & De Mulder 2003; Paillard 2003), bon (Katz 1964) and tout (Bat-Zeev Shyldkrot 1995). These two methodological tools shed light on the operation of the semantic mechanism and emphasize the relevance of the “holistic compositionality” approach when applied to idioms’ meaning construction.